2002
DOI: 10.1016/s0002-9440(10)64213-7
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating Cellular Nuclear Antigen Expression as a Marker of Perivascular Macrophages in Simian Immunodeficiency Virus Encephalitis

Abstract: Brain perivascular macrophages are a major target of simian immunodeficiency virus (SIV) infection in rhesus macaques and HIV infection in humans.Perivascular macrophages are distinct from parenchymal microglia in their location, morphology, expression of myeloid markers, and turnover in the CNS. In contrast to parenchymal microglia, perivascular macrophages are continuously repopulated by blood monocytes, which undergo maturation to macrophages on entering the central nervous system (CNS). We studied differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 51 publications
(44 reference statements)
3
63
0
Order By: Relevance
“…In support of these findings, PCNAϩ, but Ki-67Ϫ, MPs were found to be abundant in SIV-infected macaques with encephalitis (SIVE). 32 The overall increase in the number of perivascular and parenchymal MPs we observed in this study supports a model in which both perivascular and parenchymal reservoirs of HIV-1 infection accumulate as a result of increased trafficking and CNS invasion. These results emphasize the role of invading macrophages and new resident microglia as major contributors to the active reservoir of HIV-1 infection in HIVE CNS tissue.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In support of these findings, PCNAϩ, but Ki-67Ϫ, MPs were found to be abundant in SIV-infected macaques with encephalitis (SIVE). 32 The overall increase in the number of perivascular and parenchymal MPs we observed in this study supports a model in which both perivascular and parenchymal reservoirs of HIV-1 infection accumulate as a result of increased trafficking and CNS invasion. These results emphasize the role of invading macrophages and new resident microglia as major contributors to the active reservoir of HIV-1 infection in HIVE CNS tissue.…”
Section: Discussionsupporting
confidence: 85%
“…33 In our study, HIV-1 infection was clearly associated with PCNA expression in CNS, in agreement with a similar study in SIVE reported by Williams and colleagues. 32 PCNA/p24 double-labeling revealed that all cells positive for p24 were PCNAϩ. In contrast, not all PCNA-expressing cells appeared to be productively infected, in which no more than half of the PCNAϩ cells also had detectable levels of HIV-1 p24.…”
Section: Discussionmentioning
confidence: 93%
“…In Fig. 3B, representative microglial cultures illustrate a marked induction of microglial activation and proliferation during treatment with Aβ 1-42 exposed media from SH-SY5Y wildtype cells (Aβ ) as evidenced by significant PCNA expression [24] and BrdU uptake [25] when compared to microglia treated with media not exposed to Aβ 1-42 (Control). Minimal activation (PCNA) or proliferation (BRDU) of microglia is present during treatment with media from SH-SY5Y cells overexpressing Wnt1 (Wnt1/Aβ ) which are also absent of membrane PS exposure (Fig.…”
Section: Wnt1 Blocks Apoptotic Membrane Phosphatidylserine (Ps) Exposmentioning
confidence: 97%
“…[13][14][15]31 After in situ hybridization for viral nucleic acid as described above, single-or double-label immunohistochemistry or immunofluorescence was performed using a variety macrophage-and T lymphocyte-specific markers (Table 2). …”
Section: Immunophenotype Of Infected Cellsmentioning
confidence: 99%